PERAN BAHASA ARAB DALAM PENGEMBANGAN ILMU DAN PERADABAN ISLAM DI MASA DAULAH ABBASIYAH - Furoidah, Asni (UAS PRESS, 2018)
This study aims to clarify the role of the Arabic language in advancing science and Islamic civilization through a library study of the history of the Arabic language a long the ages. The approach used to analyze the data of Arabic language development is historical approach combined with content analysis approach. The study has come to the conclusion that there are ϐive important roles of Arabic language. Firstly, it served as the language of the union among the people and the Arab tribes. Secondly, Arabic preserved the richness of local Arabic cultures through all times. Thirdly, Arabic used as a media for educational and scientiϐic study, possitioning it as the language of science and technology. Fourthly, Arabic is as a tool of communication among the people and tribes and generations. Fifthly, Arabic is accepted as a standardized language for Islamic knowledge and modern sciences.